CEO TENURE AND SUSTAINABILITY PERFORMANCE: THE ROLE OF INSTITUTIONAL OWNERSHIP AND BOARD INDEPENDENCE - Septiany, Sheila; Mirabelle, Eileen; Harsono, Budi; Tang, Sukiantono; Serly; Ivone (Global Financial Accounting Journal, 2025)
Purpose – This study examines the effect of CEO tenure on sustainability performance, considering the roles of board independence and institutional ownership in companies listed on the Indonesia Stock Exchange (IDX). Research Method – The study used a purposive sampling method and collected data from annual and sustainability reports of IDX-listed companies from 2018 to 2022. Panel data regression analysis was conducted using EViews. Findings – CEO tenure has a significant positive impact on sustainability performance. CEOs with longer tenures are more effective in aligning CSR strategies with long-term goals. Board independence strengthens this effect by providing oversight, while institutional ownership improves transparency and accountability. Implication – CEO tenure supports long-term sustainability efforts. Independent boards and institutional ownership help ensure consistency and reduce the risk of managerial entrenchment.